Optimal and freely chosen paddling rate during moderate kayak ergometry - Gam, S.; Klitgaard, K. K.; Funch, A. B.; Sloth, M. E.; Holt, J. W.; Molbech, J. L.; Hansen, E. A. (Biology of Sport, 2022)
Moderate paddling, as in long distance kayaking, constitutes an endurance activity, which shares energetic aspects with activities such as long distance running and road cycling. The aim of the present study was to investigate whether in moderate paddling there is a U-shaped relationship between oxygen uptake and stroke rate, and also whether elite kayakers apply a freely chosen stroke rate, which is energetically optimal. Eleven young male elite kayakers performed moderate kayak ergometry at preset target stroke rates of 65, 75, and 90 strokes min-1, and at a freely chosen stroke rate, while physiological responses including oxygen uptake were measured. The results showed that considering average values calculated across all participants, there was an approximately U-shaped relationship between oxygen uptake and target stroke rate with a minimum at 75 strokes min-1. The freely chosen stroke rate was 67.0 ± 6.1 strokes min-1. Thus, the freely chosen stroke rate, for the group in total, appeared to be lower and require higher oxygen uptake as compared to the energetically optimal preset target stroke rate. Eight out of 11 participants had a higher oxygen uptake (5.1% ± 6.7%, p = 0.028, across all participants) at their freely chosen stroke rate than at the preset target stroke rate, which resulted in the lowest oxygen uptake. In conclusion, an approximately U-shaped relationship between oxygen uptake and stroke rate for young elite kayakers during moderate ergometer kayaking was found. Additionally, the freely chosen stroke rate was systematically lower and, consequently, required higher oxygen uptake than the preset stroke rate, which resulted in the lowest oxygen uptake.